PEMIMPIN VISIONER DALAM PERUBAHAN ORGANISASIONAL - -, Suprayitno (Universitas Slamet Riyadi, 2007)
Abstract Leader owning activity, speed and also can adapt in bringing the way organization have important role in face of condition of organization which ever experience of change. Because, organizational flexibility basically represent people who masterpiece can act proactive, creative, innovation and non conventional. Persons like this required as organizational leader in this time. A leader is change inspiration and visionary, that is have clear vision up at which organization will be brought. Keywords: visionary leader, organizational change, human resource